2008
DOI: 10.1074/jbc.m707774200
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Generation by Chlorophyllide a Reductase of Rhodobacter sphaeroides

Abstract: Chlorophyllide a reductase of Rhodobacter sphaeroides, which were reconstituted with the purified subunits of BchX, BchY, and BchZ, reduced ring B of chlorophyllide a using NADH under anaerobic conditions. Interestingly, suppressor mutations rescuing the inability of R. sphaeroides Fe-SOD mutant to grow in succinate-based minimal medium were predominantly mapped to BchZ subunit of chlorophyllide a reductase. The enzyme is labile in the presence of O 2 . However, it generates superoxide at low O 2 . The enzymes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 75 publications
4
24
0
Order By: Relevance
“…A rhombic S ϭ 1/2 signal was obtained with g values of g 1 ϭ 2.047, g 2 ϭ 1.937, and g 3 ϭ 1.905 located in a region characteristic for [4Fe-4S] 1ϩ clusters (36,37). The observed data are in agreement with related EPR experiments for the L 2 protein of DPOR (4, 38) for (NifH) 2 of Azotobacter vinelandii and also for (BchX) 2 from R. sphaeroides (g 1 ϭ 2.02, g 2 ϭ 1.93 and g 3 ϭ 1.92) (18,39). Similar to what was reported for (NifH) 2 of A. vinelandii (39), no evidence for spin states larger than S ϭ 1/2 (e.g.…”
Section: Purification and Biochemical Characterization Of R Denitrifsupporting
confidence: 78%
See 2 more Smart Citations
“…A rhombic S ϭ 1/2 signal was obtained with g values of g 1 ϭ 2.047, g 2 ϭ 1.937, and g 3 ϭ 1.905 located in a region characteristic for [4Fe-4S] 1ϩ clusters (36,37). The observed data are in agreement with related EPR experiments for the L 2 protein of DPOR (4, 38) for (NifH) 2 of Azotobacter vinelandii and also for (BchX) 2 from R. sphaeroides (g 1 ϭ 2.02, g 2 ϭ 1.93 and g 3 ϭ 1.92) (18,39). Similar to what was reported for (NifH) 2 of A. vinelandii (39), no evidence for spin states larger than S ϭ 1/2 (e.g.…”
Section: Purification and Biochemical Characterization Of R Denitrifsupporting
confidence: 78%
“…To some extent these theoretical findings are supported by a recent Rhodobacter sphaeroides study where a weak EPR signal was tentatively ascribed to a single 1ϩ cluster on (BchX) 2 or alternatively to 1ϩ clusters located on each BchX protomer (18). The individual BchY protein and also the co-purified (BchY/BchZ) 2 protein complex from R. sphaeroides showed a weak EPR signal indicative for a [3Fe-4S] 1ϩ cluster (18).…”
supporting
confidence: 67%
See 1 more Smart Citation
“…The single-crossover exconjugant (Km r ) was isolated and subjected to segregation for double crossover (bchFNB mutant, Km s ) on Sis medium containing sucrose (15%). In order to disrupt bchZ, the recombinant suicide plasmid pSUPZ100 (16) (26).…”
Section: Construction Of Mutants (I) Construction Of a Bchfnb-bchz Mmentioning
confidence: 99%
“…ChlG and ChlP have been thought to emerge through the gene duplication of BchG and BchP, respectively. Recently, we found that the COR reaction, which is specific to Bchl a biosynthesis, generates superoxide at low levels of oxygen (16), and we further proposed that the degeneration of the superoxide-generating COR step may be associated with the emergence of cyanobacterium-based Chl a biosynthesis (15).…”
mentioning
confidence: 96%